ADAPTING CYBERSECURITY KNOWLEDGE MEASURES FOR MALAYSIAN UNIVERSITY STUDENTS: INSIGHTS FROM EXPLORATORY FACTOR ANALYSIS - Salim, Nur Raidah; Mat Zin, Nur Izzati; Abu Bakar, Norhaliza; Mohd Ayub, Ahmad Fauzi (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2026)
The rise of digital threats in Malaysia underscores the need to integrate cybersecurity knowledge into higher education in STEM. However, contextually validated measurement tools remain scarce. This study adapted and validated a multidimensional instrument based on the six-dimensional Cybersecurity Scale (CS-S) framework. Following expert validation (I-CVI ≥ 0.78), the instrument was administered to 115 Malaysian STEM students. An Exploratory Factor Analysis (EFA) procedure using Principal Component Analysis (PCA) with Varimax rotation was employed to determine the factor structure. Results confirmed a robust six-component structure: Confidentiality, Integrity, Availability, Authenticity, Utility, and Possession/Control. The refined instrument demonstrated high internal consistency with a Cronbach’s Alpha of 0.80, exceeding the 0.70 threshold recommended for newly developed constructs. These findings provide a psychometrically sound foundation for subsequent Confirmatory Factor Analysis (CFA) and offer educators a reliable tool to assess cybersecurity preparedness. This research supports national digital resilience goals by providing a validated means to identify learning gaps among future STEM professionals.